A transparent powder coating for crystalline silicon of solar panels and preparation method thereof

By using acrylic resin and specific additives in solar panel crystal silicon powder coatings, combining stable multi-adjustment and doped yttrium modified nanosilicon dioxide agents, the difficulty of light transmittance and adhesion in the prior art is solved. The coordination issues significantly improve the product's salt corrosion resistance and scratch stability.

CN118755334BActive Publication Date: 2025-01-14FOSHAN TUYI DECORATIVE MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411222940.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-14
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The existing solar panel crystal silicon powder coatings have poor light transmittance performance, difficult to coordinate and improve adhesion and antifouling properties, and insufficient salt corrosion resistance and scratch stability, which limits the efficiency of the product.

Method used

Using acrylic resin as the matrix, combining curing agent, coupling agent, leveling agent and stable multi-adjustment, doped yttrium modified nanosilicon dioxide agent, coordinate the improvement of the coating's attachment through specific preparation and treatment methods. Focus on, anti-fouling performance and light transmittance, and optimize salt corrosion resistance and scratch stability.

Benefits of technology

It significantly improves the adhesion, anti-fouling performance and light transmittance of solar panel crystal silicon powder coatings, enhances the product's salt corrosion resistance and scratch stability, and achieves coordinated performance improvement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of solar panel powder coatings, and in particular to a transparent powder coating of crystalline silicon for solar panels and a preparation method thereof, comprising the following raw materials by weight: 30 to 35 parts of acrylic resin, 10 to 15 parts of curing agent, 7 to 11 parts of stabilizing and connecting multi-adjusting agent, 4 to 7 parts of yttrium-doped modified nano-silicon dioxide agent, 4 to 6 parts of coupling agent, and 2 to 5 parts of leveling agent. The transparent powder coating of the present invention adopts acrylic resin as a matrix, and by adding functional additives such as curing agent, coupling agent and leveling agent, and the added stabilizing and connecting multi-adjusting agent and yttrium-doped modified nano-silicon dioxide agent, the adhesion and antifouling performance of the product are coordinated and improved with the light transmittance, and the product has remarkable effects on salt corrosion resistance and scratch stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar panel powder coatings, and in particular to a transparent powder coating of crystalline silicon for solar panels and a preparation method thereof. Background Art

[0002] Solar panels, or solar cells, are a type of photoelectric semiconductor wafer that uses sunlight to generate electricity directly. They are also called "solar chips" or "photocells". In physics, they are called solar photovoltaics, or photovoltaics for short. As long as the illumination meets certain illumination conditions, it can instantly output voltage and generate current in the presence of a circuit. Solar cells are devices that directly convert light energy into electrical energy through the photoelectric effect or photochemical effect.

[0003] The powder coating used in existing crystalline silicon solar panels has poor light transmittance performance. In order to improve the light transmittance of the product, it is difficult to coordinate the improvement of the product's adhesion and anti-fouling performance with the light transmittance. In addition, the product's resistance to salt corrosion and scratch stability are poor, further limiting the product's efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a transparent powder coating for crystalline silicon of solar panels and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a transparent powder coating for crystalline silicon of a solar panel, comprising the following raw materials in parts by weight:

[0007] 30~35 parts of acrylic resin, 10~15 parts of curing agent, 7~11 parts of stabilizing agent, 4~7 parts of yttrium-doped nano-silica agent, 4~6 parts of coupling agent, and 2~5 parts of leveling agent.

[0008] Preferably, the acrylic resin is prepared by mixing a high epoxy equivalent acrylic resin and a low epoxy equivalent acrylic resin in a weight ratio of 3:1;

[0009] The epoxy equivalent of the high epoxy equivalent acrylic resin is 700-800 g / eq and the softening point is 90-100°C; the epoxy equivalent of the low epoxy equivalent acrylic resin is 300 g / eq, the glass transition temperature is 70°C and the molecular weight is 3000-4000;

[0010] The leveling agent is prepared by mixing polydimethylsiloxane and methyl silicone oil in a weight ratio of 1:2;

[0011] The curing agent is dodecanedioic acid; and the coupling agent is silane coupling agent KH560.

[0012] Preferably, the preparation method of the stable continuous multi-adjusting agent is:

[0013] S01: first prepare a phosphate buffer solution with a pH value of 5.0-5.5, and then mix sodium tripolyphosphate, deionized water and phosphate buffer solution in a weight ratio of 3: (5-7): 1 to obtain a sodium tripolyphosphate solution;

[0014] S02: adding 2-5 parts of tetrabutyl titanate to 4-7 parts of ethanol solvent, and then adding 1-3 parts of nano-silica sol for ultrasonic mixing, and then ending the ultrasonic treatment to obtain a modified additive solution;

[0015] S03: Preheat the nanodiamond to 65-70°C for 10-15 minutes, add 3-5 parts of the preheated nanodiamond to 4-7 parts of the modified additive solution, and then add 2-4 parts of sodium tripolyphosphate solution and mix well to obtain a continuous modified solution;

[0016] S04: adding hexagonal boron nitride to the sodium alginate solution at a weight ratio of 2:5 and mixing well to obtain a hexagonal boron nitride dispersion;

[0017] The hexagonal boron nitride dispersion and the continuous adjustment liquid are mixed in a weight ratio of 5:4 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a stable continuous multi-adjustment.

[0018] Preferably, the mass fraction of the sodium alginate solution is 4-7%.

[0019] Preferably, the ultrasonic mixing treatment has an ultrasonic power of 350-400 W and is performed for 20-30 min.

[0020] Preferably, the preparation method of the yttrium-doped modified nano-silica agent is:

[0021] S11: The nano-silicon dioxide is firstly stirred evenly in a sufficient amount of potassium permanganate solution with a mass fraction of 4-7%, then washed with water, dried, and then irradiated in a proton irradiation box. After the irradiation is completed, a nano-silicon dioxide agent is obtained;

[0022] S12: adding 3-5 parts of nano-silica to 4-7 parts of 5% by mass yttrium nitrate solution, and then adding 2-3 parts of silane coupling agent KH550 and 1-3 parts of 5-6% by mass chitosan solution to fully obtain a yttrium-doped modifier;

[0023] S13: Mix the coordination enhancer and the yttrium-doped modifier in a weight ratio of (2-3):5 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a yttrium-doped modified nano-silica agent.

[0024] Preferably, the irradiation power of the irradiation treatment is 350-400 W, and the irradiation time is 5-10 min; the ball milling speed of the mixed ball milling treatment is 750-850 r / min, and the ball milling time is 2 h.

[0025] Preferably, the preparation method of the synergist is:

[0026] The nano-titanium dioxide is first immersed in a zinc sulfate solution with a volume of 3 to 5 times the total volume of the nano-titanium dioxide for ultrasonic immersion treatment, and after the immersion is completed, the solution is filtered and dried to obtain a nano-titanium dioxide modifier;

[0027] Add 3-5 parts of nano titanium dioxide modifier to 4-6 parts of lanthanum chloride solution, and then add 1-3 parts of sodium dodecylbenzene sulfonate, 2-4 parts of nano alumina and 0.6-0.8 parts of stearic acid to mix and ball mill thoroughly. The ball milling speed is 1000-1500r / min, and the ball milling is carried out for 2h. After the ball milling is completed, wash with water and dry to obtain a coordination enhancer.

[0028] Preferably, the mass fraction of the zinc sulfate solution is 3-6%; the mass fraction of the lanthanum chloride solution is 2-5%; the ultrasonic power of the ultrasonic immersion treatment is 400-450 W, and the ultrasonic time is 20-30 min.

[0029] The present invention also provides a method for preparing a transparent powder coating of crystalline silicon for solar panels, comprising the following steps:

[0030] The raw materials are weighed according to weight, mixed evenly, melt-extruded at 105° C., tableted, crushed, and passed through a 100-mesh sieve to obtain the powder coating of the present invention.

[0031] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0032] 1. The transparent powder coating of the present invention adopts acrylic resin as the matrix, and the functional additives such as curing agent, coupling agent and leveling agent are added, and the added stabilizing agent and yttrium-doped modified nano-silica agent are coordinated and synergistic, so that the adhesion and antifouling performance of the product are coordinated and improved with the light transmittance, and the salt corrosion resistance and scratch stability of the product are significantly improved;

[0033] 2. The stabilizing continuous multi-adjusting agent is prepared by blending sodium tripolyphosphate, deionized water and phosphate buffer solution to obtain sodium tripolyphosphate liquid, and the modified additive liquid is obtained by ultrasonic mixing with tetrabutyl titanate, ethanol solvent and nano-silica sol. The nano-diamond is preheated to 65-70°C, and then the modified additive liquid and the sodium tripolyphosphate liquid are blended and coordinated. The nano-diamond is used as a matrix to distribute in the matrix, thereby co-combining hexagonal boron nitride. The hexagonal boron nitride is coordinated and dispersed with the sodium alginate solution to increase the dispersion of the hexagonal boron nitride, so as to facilitate better coordination and coordination with the nano-diamond in the continuous adjustment of the modified liquid system. At the same time, after the continuous adjustment of the modified liquid of the present invention, the prepared stabilizing continuous multi-adjusting agent can coordinate and balance the adhesion, anti-fouling performance and light transmittance of the system, and optimize the salt corrosion resistance and scratch stability of the product;

[0034] 3. Yttrium-doped modified nano-silica agent: Nano-silica is firstly stirred evenly in potassium permanganate solution, and then irradiated in a proton irradiation box to optimize the activity performance of nano-silica. At the same time, yttrium nitrate solution, silane coupling agent KH550 and chitosan solution with a mass fraction of 5-6% are fully blended to obtain a yttrium-doped modifier. The raw materials in the yttrium-doped modifier are blended with each other to prepare nano-silica, optimize the dispersion of nano-silica, and improve the coordination and synergy effect of the yttrium-doped modifier and the coordination enhancer, thereby improving the performance of the product;

[0035] 4. The coordination and strengthening agent adopts nano titanium dioxide which is first immersed in a zinc sulfate solution and ultrasonically immersed to obtain zinc-doped nano titanium dioxide. At the same time, it is fully blended and ball-milled with lanthanum chloride solution, sodium dodecylbenzene sulfonate, nano alumina and stearic acid. Nano alumina is coordinated with the zinc-doped nano titanium dioxide and the raw materials in the synergistic coordination and strengthening agent. Through the coordination between the raw materials, the adhesion and anti-fouling performance of the product system are enhanced, and the light transmittance is coordinated and improved, as well as the salt corrosion resistance and scratch stability of the product are improved. DETAILED DESCRIPTION

[0036] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] A transparent powder coating for crystalline silicon of a solar panel of this embodiment includes the following raw materials in parts by weight:

[0038] 30~35 parts of acrylic resin, 10~15 parts of curing agent, 7~11 parts of stabilizing agent, 4~7 parts of yttrium-doped nano-silica agent, 4~6 parts of coupling agent, and 2~5 parts of leveling agent.

[0039] The acrylic resin in this embodiment is prepared by mixing a high epoxy equivalent acrylic resin and a low epoxy equivalent acrylic resin in a weight ratio of 3:1;

[0040] The epoxy equivalent of the high epoxy equivalent acrylic resin is 700-800 g / eq and the softening point is 90-100°C; the epoxy equivalent of the low epoxy equivalent acrylic resin is 300 g / eq, the glass transition temperature is 70°C and the molecular weight is 3000-4000;

[0041] The leveling agent is prepared by mixing polydimethylsiloxane and methyl silicone oil in a weight ratio of 1:2;

[0042] The curing agent is dodecanedioic acid; and the coupling agent is silane coupling agent KH560.

[0043] The preparation method of the stable continuous multi-adjusting agent of this embodiment is:

[0044] S01: first prepare a phosphate buffer solution with a pH value of 5.0-5.5, and then mix sodium tripolyphosphate, deionized water and phosphate buffer solution in a weight ratio of 3: (5-7): 1 to obtain a sodium tripolyphosphate solution;

[0045] S02: adding 2-5 parts of tetrabutyl titanate to 4-7 parts of ethanol solvent, and then adding 1-3 parts of nano-silica sol for ultrasonic mixing, and then ending the ultrasonic treatment to obtain a modified additive solution;

[0046] S03: Preheat the nanodiamond to 65-70°C for 10-15 minutes, add 3-5 parts of the preheated nanodiamond to 4-7 parts of the modified additive solution, and then add 2-4 parts of sodium tripolyphosphate solution and mix well to obtain a continuous modified solution;

[0047] S04: adding hexagonal boron nitride to the sodium alginate solution at a weight ratio of 2:5 and mixing well to obtain a hexagonal boron nitride dispersion;

[0048] The hexagonal boron nitride dispersion and the continuous adjustment liquid are mixed in a weight ratio of 5:4 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a stable continuous multi-adjustment.

[0049] The mass fraction of the sodium alginate solution in this embodiment is 4-7%.

[0050] The ultrasonic mixing treatment in this embodiment has an ultrasonic power of 350-400 W and an ultrasonic treatment time of 20-30 min.

[0051] The preparation method of the yttrium-doped nano-silica agent of this embodiment is as follows:

[0052] S11: The nano-silicon dioxide is firstly stirred evenly in a sufficient amount of potassium permanganate solution with a mass fraction of 4-7%, then washed with water, dried, and then irradiated in a proton irradiation box. After the irradiation is completed, a nano-silicon dioxide agent is obtained;

[0053] S12: adding 3-5 parts of nano-silica to 4-7 parts of 5% by mass yttrium nitrate solution, and then adding 2-3 parts of silane coupling agent KH550 and 1-3 parts of 5-6% by mass chitosan solution to fully obtain a yttrium-doped modifier;

[0054] S13: Mix the coordination enhancer and the yttrium-doped modifier in a weight ratio of (2-3):5 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a yttrium-doped modified nano-silica agent.

[0055] The irradiation power of the irradiation treatment in this embodiment is 350-400W, and the irradiation time is 5-10 minutes; the ball milling speed of the mixed ball milling treatment is 750-850r / min, and the ball milling time is 2 hours.

[0056] The preparation method of the coordination enhancer of this embodiment is:

[0057] The nano-titanium dioxide is first immersed in a zinc sulfate solution with a volume of 3 to 5 times the total volume of the nano-titanium dioxide for ultrasonic immersion treatment, and after the immersion is completed, the solution is filtered and dried to obtain a nano-titanium dioxide modifier;

[0058] Add 3-5 parts of nano titanium dioxide modifier to 4-6 parts of lanthanum chloride solution, and then add 1-3 parts of sodium dodecylbenzene sulfonate, 2-4 parts of nano alumina and 0.6-0.8 parts of stearic acid to mix and ball mill thoroughly. The ball milling speed is 1000-1500r / min, and the ball milling is carried out for 2h. After the ball milling is completed, wash with water and dry to obtain a coordination enhancer.

[0059] The mass fraction of the zinc sulfate solution in this embodiment is 3-6%; the mass fraction of the lanthanum chloride solution is 2-5%; the ultrasonic power of the ultrasonic immersion treatment is 400-450W, and the ultrasonic time is 20-30min.

[0060] The method for preparing a transparent powder coating of crystalline silicon for solar panels of the present embodiment comprises the following steps:

[0061] The raw materials are weighed according to weight, mixed evenly, melt-extruded at 105° C., tableted, crushed, and passed through a 100-mesh sieve to obtain the powder coating of the present invention.

[0062] Example 1.

[0063] A transparent powder coating for crystalline silicon of a solar panel of this embodiment includes the following raw materials in parts by weight:

[0064] 30 parts of acrylic resin, 10 parts of curing agent, 7 parts of stabilizing agent, 4 parts of yttrium-doped nano-silica agent, 4 parts of coupling agent, and 2 parts of leveling agent.

[0065] The acrylic resin in this embodiment is prepared by mixing a high epoxy equivalent acrylic resin and a low epoxy equivalent acrylic resin in a weight ratio of 3:1;

[0066] The epoxy equivalent of the high epoxy equivalent acrylic resin is 700 g / eq and the softening point is 90°C; the epoxy equivalent of the low epoxy equivalent acrylic resin is 300 g / eq, the glass transition temperature is 70°C and the molecular weight is 3000;

[0067] The leveling agent is prepared by mixing polydimethylsiloxane and methyl silicone oil in a weight ratio of 1:2;

[0068] The curing agent is dodecanedioic acid; and the coupling agent is silane coupling agent KH560.

[0069] The preparation method of the stable continuous multi-adjusting agent of this embodiment is:

[0070] S01: first prepare a phosphate buffer solution with a pH value of 5.0, and then mix sodium tripolyphosphate, deionized water and the phosphate buffer solution in a weight ratio of 3:5:1 to obtain a sodium tripolyphosphate solution;

[0071] S02: adding 2 parts of tetrabutyl titanate to 4 parts of ethanol solvent, and then adding 1 part of nano-silica sol for ultrasonic mixing, and ending the ultrasonic treatment to obtain a modified additive solution;

[0072] S03: preheat the nanodiamond to 65°C for 10 minutes, add 3 parts of the preheated nanodiamond to 4 parts of the modified additive solution, and then add 2 parts of sodium tripolyphosphate solution and mix well to obtain a continuous modified solution;

[0073] S04: adding hexagonal boron nitride to the sodium alginate solution at a weight ratio of 2:5 and mixing well to obtain a hexagonal boron nitride dispersion;

[0074] The hexagonal boron nitride dispersion and the continuous adjustment liquid were mixed in a weight ratio of 5:4 and ball-milled at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water and dried to obtain a stable continuous multi-adjustment agent.

[0075] The mass fraction of the sodium alginate solution in this embodiment is 4%.

[0076] The ultrasonic power of the ultrasonic mixing treatment in this embodiment is 350W, and the ultrasonication is performed for 20 minutes.

[0077] The preparation method of the yttrium-doped nano-silica agent of this embodiment is as follows:

[0078] S11: The nano-silicon dioxide is firstly stirred evenly in a sufficient amount of a potassium permanganate solution having a mass fraction of 4%, then washed with water, dried, and then irradiated in a proton irradiation box. After the irradiation is completed, a nano-silicon dioxide agent is obtained;

[0079] S12: adding 3 parts of nano-silica to 4 parts of 5% by mass yttrium nitrate solution, and then adding 2 parts of silane coupling agent KH550 and 1 part of 5% by mass chitosan solution to fully blend to obtain a yttrium-doped modifier;

[0080] S13: Mix the coordination enhancer and the yttrium-doped modifier in a weight ratio of 2:5 and subject them to ball milling. After the ball milling is completed, wash with water and dry to obtain a yttrium-doped modified nano-silica agent.

[0081] The irradiation power of the irradiation treatment in this embodiment is 350W, and the irradiation time is 5 minutes; the ball milling speed of the mixed ball milling treatment is 750r / min, and the ball milling time is 2 hours.

[0082] The preparation method of the coordination enhancer of this embodiment is:

[0083] The nano-titanium dioxide is first immersed in a zinc sulfate solution with a volume three times the total volume of the nano-titanium dioxide for ultrasonic immersion treatment, and after the immersion is completed, the solution is filtered and dried to obtain a nano-titanium dioxide modifier;

[0084] Add 3 parts of nano titanium dioxide modifier to 4 parts of lanthanum chloride solution, then add 1 part of sodium dodecylbenzene sulfonate, 2 parts of nano alumina and 0.6 parts of stearic acid and mix them thoroughly with ball mill at a speed of 1000 r / min for 2 hours. After the ball milling is completed, wash with water and dry to obtain a coordination enhancer.

[0085] The mass fraction of the zinc sulfate solution in this embodiment is 3%; the mass fraction of the lanthanum chloride solution is 2%; the ultrasonic power of the ultrasonic immersion treatment is 400W, and the ultrasonic time is 20min.

[0086] The method for preparing a transparent powder coating of crystalline silicon for solar panels of the present embodiment comprises the following steps:

[0087] The raw materials are weighed according to weight, mixed evenly, melt-extruded at 105° C., tableted, crushed, and passed through a 100-mesh sieve to obtain the powder coating of the present invention.

[0088] Example 2.

[0089] A transparent powder coating for crystalline silicon of a solar panel of this embodiment includes the following raw materials in parts by weight:

[0090] 35 parts of acrylic resin, 15 parts of curing agent, 11 parts of stabilizing agent, 7 parts of yttrium-doped nano-silica agent, 6 parts of coupling agent, and 5 parts of leveling agent.

[0091] The acrylic resin in this embodiment is prepared by mixing a high epoxy equivalent acrylic resin and a low epoxy equivalent acrylic resin in a weight ratio of 3:1;

[0092] The epoxy equivalent of the high epoxy equivalent acrylic resin is 800 g / eq and the softening point is 100° C.; the epoxy equivalent of the low epoxy equivalent acrylic resin is 300 g / eq, the glass transition temperature is 70° C. and the molecular weight is 34,000;

[0093] The leveling agent is prepared by mixing polydimethylsiloxane and methyl silicone oil in a weight ratio of 1:2;

[0094] The curing agent is dodecanedioic acid; and the coupling agent is silane coupling agent KH560.

[0095] The preparation method of the stable continuous multi-adjusting agent of this embodiment is:

[0096] S01: first prepare a phosphate buffer solution with a pH value of 5.5, and then mix sodium tripolyphosphate, deionized water and the phosphate buffer solution in a weight ratio of 3:7:1 to obtain a sodium tripolyphosphate solution;

[0097] S02: adding 5 parts of tetrabutyl titanate to 7 parts of ethanol solvent, and then adding 3 parts of nano-silica sol for ultrasonic mixing, and ending the ultrasonic treatment to obtain a modified additive solution;

[0098] S03: preheat the nanodiamond to 70°C for 15 minutes, add 5 parts of the preheated nanodiamond to 7 parts of the modified additive solution, and then add 4 parts of sodium tripolyphosphate solution and mix well to obtain a continuous modified solution;

[0099] S04: adding hexagonal boron nitride to the sodium alginate solution at a weight ratio of 2:5 and mixing well to obtain a hexagonal boron nitride dispersion;

[0100] The hexagonal boron nitride dispersion and the continuous adjustment liquid were mixed in a weight ratio of 5:4 and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water and dried to obtain a stable continuous multi-adjustment agent.

[0101] The mass fraction of the sodium alginate solution in this embodiment is 7%.

[0102] The ultrasonic power of the ultrasonic mixing treatment in this embodiment is 400W, and the ultrasonic mixing is performed for 30 minutes.

[0103] The preparation method of the yttrium-doped nano-silica agent of this embodiment is as follows:

[0104] S11: The nano-silicon dioxide is firstly stirred evenly in a sufficient amount of a potassium permanganate solution having a mass fraction of 7%, then washed with water, dried, and then irradiated in a proton irradiation box. After the irradiation is completed, a nano-silicon dioxide agent is obtained;

[0105] S12: adding 5 parts of nano-silica to 7 parts of 5% by mass yttrium nitrate solution, and then adding 3 parts of silane coupling agent KH550 and 3 parts of 6% by mass chitosan solution to fully blend to obtain a yttrium-doped modifier;

[0106] S13: Mix the coordination enhancer and the yttrium-doped modifier in a weight ratio of 3:5 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a yttrium-doped modified nano-silica agent.

[0107] The irradiation power of the irradiation treatment in this embodiment is 400W, and the irradiation time is 10 minutes; the ball milling speed of the mixed ball milling treatment is 850r / min, and the ball milling time is 2 hours.

[0108] The preparation method of the coordination enhancer of this embodiment is:

[0109] The nano-titanium dioxide is first immersed in a zinc sulfate solution with a volume 5 times the total volume of the nano-titanium dioxide for ultrasonic immersion treatment, and after the immersion is completed, the solution is filtered and dried to obtain a nano-titanium dioxide modifier;

[0110] Add 5 parts of nano titanium dioxide modifier to 6 parts of lanthanum chloride solution, then add 3 parts of sodium dodecylbenzene sulfonate, 4 parts of nano alumina and 0.8 parts of stearic acid and mix them thoroughly with ball mill at a speed of 1500r / min for 2h. After the ball milling is completed, wash with water and dry to obtain a coordination enhancer.

[0111] The mass fraction of the zinc sulfate solution in this embodiment is 6%; the mass fraction of the lanthanum chloride solution is 5%; the ultrasonic power of the ultrasonic immersion treatment is 450W, and the ultrasonic time is 30min.

[0112] The method for preparing a transparent powder coating of crystalline silicon for solar panels of the present embodiment comprises the following steps:

[0113] The raw materials are weighed according to weight, mixed evenly, melt-extruded at 105° C., tableted, crushed, and passed through a 100-mesh sieve to obtain the powder coating of the present invention.

[0114] Example 3.

[0115] A transparent powder coating for crystalline silicon of a solar panel of this embodiment includes the following raw materials in parts by weight:

[0116] 32.5 parts of acrylic resin, 12.5 parts of curing agent, 9 parts of stabilizing agent, 5.5 parts of yttrium-doped nano-silica agent, 5 parts of coupling agent, and 3.5 parts of leveling agent.

[0117] The acrylic resin in this embodiment is prepared by mixing a high epoxy equivalent acrylic resin and a low epoxy equivalent acrylic resin in a weight ratio of 3:1;

[0118] The epoxy equivalent of the high epoxy equivalent acrylic resin is 700-800 g / eq and the softening point is 95°C; the epoxy equivalent of the low epoxy equivalent acrylic resin is 300 g / eq, the glass transition temperature is 70°C and the molecular weight is 3500;

[0119] The leveling agent is prepared by mixing polydimethylsiloxane and methyl silicone oil in a weight ratio of 1:2;

[0120] The curing agent is dodecanedioic acid; and the coupling agent is silane coupling agent KH560.

[0121] The preparation method of the stable continuous multi-adjusting agent of this embodiment is:

[0122] S01: first prepare a phosphate buffer solution with a pH value of 5.2, and then mix sodium tripolyphosphate, deionized water and the phosphate buffer solution in a weight ratio of 3:6:1 to obtain a sodium tripolyphosphate solution;

[0123] S02: 3.5 parts of tetrabutyl titanate are added to 5.5 parts of ethanol solvent, and then 2 parts of nano-silica sol are added and ultrasonically mixed. After the ultrasonic treatment is terminated, a modified additive solution is obtained;

[0124] S03: preheat the nanodiamond to 67°C for 12 minutes, add 4 parts of the preheated nanodiamond to 5.5 parts of the modified additive solution, and then add 3 parts of sodium tripolyphosphate solution and mix well to obtain a continuous modified solution;

[0125] S04: adding hexagonal boron nitride to the sodium alginate solution at a weight ratio of 2:5 and mixing well to obtain a hexagonal boron nitride dispersion;

[0126] The hexagonal boron nitride dispersion and the continuous adjustment liquid were mixed in a weight ratio of 5:4 and ball-milled at a speed of 1250 r / min for 2 h. After the ball milling was completed, the mixture was washed with water and dried to obtain a stable continuous multi-adjustment agent.

[0127] The mass fraction of the sodium alginate solution in this embodiment is 5.5%.

[0128] The ultrasonic mixing treatment in this embodiment was performed with an ultrasonic power of 370 W and for 25 min.

[0129] The preparation method of the yttrium-doped nano-silica agent of this embodiment is as follows:

[0130] S11: The nano-silicon dioxide is firstly stirred evenly in a sufficient amount of a potassium permanganate solution with a mass fraction of 5.5%, then washed with water, dried, and then irradiated in a proton irradiation box. After the irradiation is completed, a nano-silicon dioxide agent is obtained;

[0131] S12: adding 4 parts of nano-silica to 5.5 parts of 5% by mass yttrium nitrate solution, and then adding 2.5 parts of silane coupling agent KH550 and 2 parts of 5.5% by mass chitosan solution to fully mix to obtain a yttrium-doped modifier;

[0132] S13: Mix the coordination enhancer and the yttrium-doped modifier in a weight ratio of 1:2 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a yttrium-doped modified nano-silica agent.

[0133] The irradiation power of the irradiation treatment in this embodiment is 370W, and the irradiation time is 7.5min; the ball milling speed of the mixed ball milling treatment is 800r / min, and the ball milling time is 2h.

[0134] The preparation method of the coordination enhancer of this embodiment is:

[0135] The nano-titanium dioxide is first immersed in a zinc sulfate solution with a volume 4 times the total volume of the nano-titanium dioxide for ultrasonic immersion treatment, and after the immersion is completed, the solution is filtered and dried to obtain a nano-titanium dioxide modifier;

[0136] Add 4 parts of nano titanium dioxide modifier to 5 parts of lanthanum chloride solution, and then add 2 parts of sodium dodecylbenzene sulfonate, 3 parts of nano alumina and 0.7 parts of stearic acid to mix and ball mill thoroughly. The ball milling speed is 1250r / min, and the ball milling is carried out for 2h. After the ball milling is completed, wash with water and dry to obtain a coordination enhancer.

[0137] The mass fraction of the zinc sulfate solution in this embodiment is 4.5%; the mass fraction of the lanthanum chloride solution is 3.5%; the ultrasonic power of the ultrasonic immersion treatment is 425W, and the ultrasonic time is 25min.

[0138] The method for preparing a transparent powder coating of crystalline silicon for solar panels of the present embodiment comprises the following steps: weighing raw materials according to weight, mixing the raw materials evenly, then melt-extruding at 105° C., tableting, crushing, and passing through a 100-mesh sieve to obtain the powder coating of the present invention.

[0139] Comparative Example 1.

[0140] The difference from Example 3 is that no stabilizing agent is added.

[0141] Comparative Example 2.

[0142] The difference from Example 3 is that no continuous adjustment and modification liquid treatment is used in the preparation of the stable continuous multi-adjusting agent.

[0143] Comparative Example 3.

[0144] The difference from Example 3 is that no preheated nano-diamonds are added to the continuous conditioning modification solution.

[0145] Comparative Example 4.

[0146] The difference from Example 3 is that no modifying additive liquid is added to the continuously adjusted modifying liquid.

[0147] Comparative Example 5.

[0148] The difference from Example 3 is that no sodium tripolyphosphate solution is added to the continuous adjustment modification liquid.

[0149] Comparative Example 6.

[0150] The difference from Example 3 is that no hexagonal boron nitride dispersion was added during the preparation of the stable and continuous multi-adjusting agent.

[0151] Comparative Example 7.

[0152] The difference from Example 3 is that no yttrium-doped modified nano-silica agent is added.

[0153] Comparative Example 8.

[0154] The difference from Example 3 is that no nano-silica agent is added in the preparation of the yttrium-doped modified nano-silica agent.

[0155] Comparative Example 9.

[0156] The difference from Example 3 is that the silane coupling agent KH550 and the chitosan solution with a mass fraction of 5.5% are not added in the preparation of the yttrium-doped modified nano-silica agent.

[0157] Comparative Example 10.

[0158] The difference from Example 3 is that no coordination enhancer is added in the preparation of the yttrium-doped modified nano-silica agent.

[0159] The products of Examples 1 to 3 and Comparative Examples 1 to 10 were sprayed on a substrate using an electrostatic spraying technique, with a spraying thickness of 50 μm. The coatings were subjected to conventional performance tests, and the test results are shown in Table 1, which is a performance test table of light transmittance, adhesion, and antifouling grade;

[0160] Table 1:

[0161]

[0162] The product was placed in a 5% sodium chloride salt spray environment for 12 hours, and then a scratching force of 10N load was applied for 10 times to test the product's salt corrosion resistance and scratch stability. Table 2 is a performance test table of light transmittance, adhesion and antifouling grade under salt corrosion resistance and scratch conditions. The test results are shown in Table 2;

[0163] Table 2:

[0164]

[0165] It can be seen from Comparative Examples 1-10 and Examples 1-3 that;

[0166] The product of Example 3 has excellent light transmittance performance, and at the same time, excellent coating adhesion and antifouling grade performance. The product can achieve coordinated improvement in light transmittance, adhesion and antifouling performance. In addition, the product has excellent performance stability under salt corrosion and scratching conditions;

[0167] The product does not add any of the stabilizer and yttrium-doped nano-silica agent, and the performance of the product deteriorates significantly. The synergistic effect of the two is the most significant.

[0168] In the preparation of the steady-state continuous multi-adjusting agent, the continuous adjustment modifying liquid was not used for treatment, the preheated nanodiamond was not added to the continuous adjustment modifying liquid, the modifying additive liquid was not added to the continuous adjustment modifying liquid, the sodium tripolyphosphate liquid was not added to the continuous adjustment modifying liquid, and the hexagonal boron nitride dispersion liquid was not added for treatment. The performance of the product tended to deteriorate. The steady-state continuous multi-adjusting agent prepared by the continuous adjustment modifying liquid obtained by the method of the present invention and the hexagonal boron nitride dispersion liquid treatment had the most significant product performance effect.

[0169] The performance effects of the products without adding nano-silica agent, silane coupling agent KH550, 5.5% chitosan solution by mass, and yttrium-doped modified nano-silica agent all tend to deteriorate in the preparation of the yttrium-doped modified nano-silica agent, and only the yttrium-doped modified nano-silica agent obtained by the method of the present invention has the most significant product performance effect. Other methods are not as obvious as the effects of the present invention, and the absence of a synergistic agent has a significant effect on the salt corrosion resistance and scratch stability of the product.

[0170] Based on the trend that the coordination enhancer has a greater impact on product performance, the present invention further explores the product performance through the preparation of the coordination enhancer;

[0171] Experimental example 1.

[0172] The only difference from Example 3 is that no nano titanium dioxide modifier is added in the preparation of the coordination enhancer.

[0173] Experimental example 2.

[0174] The only difference from Example 3 is that the nano-titanium dioxide modifier is not subjected to ultrasonic immersion treatment in a zinc sulfate solution.

[0175] Experimental Example 3.

[0176] The only difference from Example 3 is that no nano-alumina is added in the preparation of the coordination enhancer.

[0177] Experimental Example 4.

[0178] The only difference from Example 3 is that the lanthanum chloride solution is replaced by deionized water.

[0179] Experimental Example 5.

[0180] The only difference from Example 3 is that sodium dodecylbenzene sulfonate and stearic acid are not added in the preparation of the coordination enhancer.

[0181] Taking the above test conditions of salt corrosion resistance and scratch resistance as the test object, the effect of the preparation of the coordination agent on the performance of the product was tested. The test results are shown in Table 3 below. Table 3 is a performance test table of the coordination agent on transmittance, adhesion and antifouling grade under the conditions of salt corrosion resistance and scratch resistance;

[0182] Table 3:

[0183]

[0184] It can be seen from Experimental Examples 1-5 that no nano-titanium dioxide modifier is added in the preparation of the coordination effect enhancer. The performance changes of the product are most obvious in the preparation of the coordination effect enhancer, followed by no addition of nano-alumina. At the same time, the nano-titanium dioxide modifier is not treated with ultrasonic immersion in zinc sulfate solution, deionized water is not used instead of lanthanum chloride solution, and sodium dodecylbenzene sulfonate and stearic acid are not added in the preparation of the coordination effect enhancer. The performance of the product has a tendency to deteriorate to varying degrees. The specific coordination effect enhancer of the present invention is used, and the product performance effect is the most significant. The use of other methods is not as obvious as the effect of the present invention.

[0185] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0186] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A transparent powder coating for crystalline silicon of solar panels, characterized in that: It includes the following raw materials in parts by weight: 30~35 parts of acrylic resin, 10~15 parts of curing agent, 7~11 parts of stabilizing agent, 4~7 parts of yttrium-doped nano-silica agent, 4~6 parts of coupling agent, 2~5 parts of leveling agent; The preparation method of the stable continuous multi-adjusting agent is as follows: S01: first prepare a phosphate buffer solution with a pH value of 5.0-5.5, and then mix sodium tripolyphosphate, deionized water and phosphate buffer solution in a weight ratio of 3: (5-7): 1 to obtain a sodium tripolyphosphate solution; S02: adding 2-5 parts of tetrabutyl titanate to 4-7 parts of ethanol solvent, and then adding 1-3 parts of nano-silica sol for ultrasonic mixing, and then ending the ultrasonic treatment to obtain a modified additive solution; S03: Preheat the nanodiamond to 65-70°C for 10-15 minutes, add 3-5 parts of the preheated nanodiamond to 4-7 parts of the modified additive solution, and then add 2-4 parts of sodium tripolyphosphate solution and mix well to obtain a continuous modified solution; S04: adding hexagonal boron nitride to the sodium alginate solution at a weight ratio of 2:5 and mixing well to obtain a hexagonal boron nitride dispersion; The hexagonal boron nitride dispersion and the continuous adjustment liquid are mixed in a weight ratio of 5:4 and ball milled at a ball milling speed of 1000-1500 r / min for 2 hours. After the ball milling is completed, the mixture is washed with water and dried to obtain a stable continuous multi-adjustment agent. The preparation method of the yttrium-doped modified nano-silica agent: S11: The nano-silicon dioxide is firstly stirred evenly in a sufficient amount of potassium permanganate solution with a mass fraction of 4-7%, then washed with water, dried, and then irradiated in a proton irradiation box. After the irradiation is completed, a nano-silicon dioxide agent is obtained; S12: adding 3-5 parts of nano-silica to 4-7 parts of 5% by mass yttrium nitrate solution, and then adding 2-3 parts of silane coupling agent KH550 and 1-3 parts of 5-6% by mass chitosan solution to fully obtain a yttrium-doped modifier; S13: mixing the coordination enhancer and the yttrium-doped modifier in a weight ratio of (2-3):5 and subjecting them to ball milling. After the ball milling is completed, washing and drying are performed to obtain a yttrium-doped modified nano-silica agent. The preparation method of the coordination effect enhancer is: The nano-titanium dioxide is first immersed in a zinc sulfate solution with a volume of 3 to 5 times the total volume of the nano-titanium dioxide for ultrasonic immersion treatment, and after the immersion is completed, the solution is filtered and dried to obtain a nano-titanium dioxide modifier; Add 3-5 parts of nano titanium dioxide modifier to 4-6 parts of lanthanum chloride solution, and then add 1-3 parts of sodium dodecylbenzene sulfonate, 2-4 parts of nano alumina and 0.6-0.8 parts of stearic acid to mix and ball mill thoroughly. The ball milling speed is 1000-1500r / min, and the ball milling is carried out for 2h. After the ball milling is completed, wash with water and dry to obtain a coordination enhancer.

2. The transparent powder coating for crystalline silicon of solar panels according to claim 1, characterized in that: The acrylic resin is prepared by mixing a high epoxy equivalent acrylic resin and a low epoxy equivalent acrylic resin in a weight ratio of 3:1; The epoxy equivalent of the high epoxy equivalent acrylic resin is 700-800 g / eq and the softening point is 90-100°C; the epoxy equivalent of the low epoxy equivalent acrylic resin is 300 g / eq, the glass transition temperature is 70°C and the molecular weight is 3000-4000; The leveling agent is prepared by mixing polydimethylsiloxane and methyl silicone oil in a weight ratio of 1:2; The curing agent is dodecanedioic acid; the coupling agent is silane coupling agent KH560.

3. The transparent powder coating for crystalline silicon of solar panels according to claim 1, characterized in that: The mass fraction of the sodium alginate solution is 4-7%.

4. The transparent powder coating for crystalline silicon of solar panels according to claim 1, characterized in that: The ultrasonic mixing treatment is performed at an ultrasonic power of 350-400 W and for 20-30 min.

5. The transparent powder coating for crystalline silicon of solar panels according to claim 1, characterized in that: The irradiation power of the irradiation treatment is 350-400W, and the irradiation time is 5-10 minutes; the ball milling speed of the mixed ball milling treatment is 750-850r / min, and the ball milling time is 2 hours.

6. The transparent powder coating for crystalline silicon of solar panels according to claim 1, characterized in that: The mass fraction of the zinc sulfate solution is 3-6%; the mass fraction of the lanthanum chloride solution is 2-5%; the ultrasonic power of the ultrasonic immersion treatment is 400-450W, and the ultrasonic time is 20-30min.

7. A method for preparing a transparent powder coating of crystalline silicon for solar panels according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials were weighed according to weight, mixed evenly, and then melt-extruded at 105° C., tableted, crushed, and passed through a 100-mesh sieve to obtain a transparent powder coating.

Citation Information

Patent Citations

  • High-weather resistant antifouling acrylic resin powder coating and preparation method thereof

    CN111393939A

  • Transparent powder coating for photovoltaic panel adhesive film and preparation method of transparent powder coating

    CN116814127A